2017
DOI: 10.12659/msm.903056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electro-Acupuncture on Neuroplasticity of Spinal Cord-Transected Rats

Abstract: BackgroundThis study aimed to evaluate the effects of electro-acupuncture (EA) on neuroplasticity associated with the expressions of neurotrophic factors (NTFs) and their receptors in rats subjected to spinal cord transection (SCT).Material/MethodsA total of 144 rats were randomly divided into 3 groups (n=48 per group): sham-operated group, SCT group, and EA (electro-acupuncture) group. Rats in SCT and EA groups received spinal cord transection at T10–T11 vertebral levels. Then, EA group rats received EA treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…Additional reports have shown that EA-induced increases in the expression of IGF-1 in the spared L6 DRG and associated dorsal horns may be associated with the intraspinal sprouting of DRG neurons in de-afferentated cats subjected to adjacent dorsal root ganglionectomies (26). Therefore, the enhanced CGRP- and GAP-43-IRs observed in the present study suggests that nerve regeneration, cone regrowth and synaptic formation were promoted in the de-afferentated spinal cord following EA treatment, and this may be used to reconstruct local circuitry for further functional recovery (9,45). The results of the present study also demonstrated that the overexpression of IGF-1 promoted EA-induced neuroplasticity and that IGF-1 siRNA treatment weakened this effect.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Additional reports have shown that EA-induced increases in the expression of IGF-1 in the spared L6 DRG and associated dorsal horns may be associated with the intraspinal sprouting of DRG neurons in de-afferentated cats subjected to adjacent dorsal root ganglionectomies (26). Therefore, the enhanced CGRP- and GAP-43-IRs observed in the present study suggests that nerve regeneration, cone regrowth and synaptic formation were promoted in the de-afferentated spinal cord following EA treatment, and this may be used to reconstruct local circuitry for further functional recovery (9,45). The results of the present study also demonstrated that the overexpression of IGF-1 promoted EA-induced neuroplasticity and that IGF-1 siRNA treatment weakened this effect.…”
Section: Discussionmentioning
confidence: 58%
“…CGRP and GAP-43 serve key roles in regenerative neurite growth following spinal lesions (9). As a well-known marker for sensory axons transmitting pain sensations, the increased expression of CGRP is associated with nerve regeneration following lesion (44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations